Scaling up of livestock production for sustainable livelihood: An empirical study from Sirajganj district of Bangladesh: Scaling up of livestock production in Sirajganj district - Rana, Md Masud; Murshed, Hasan Mohammad; Roy, Debashis; Huda, Md Nazmul (SAARC Journal of Agriculture, 2022)
Livestock is a vital component of the complex farming system in Bangladesh. This focuses towards he contribution of livestock farming in the livelihood of the farmers as well as the realization of the challenges in livestock farming as perceived by the farmers. A mixed-method research design was used to collect data from 100 livestock farmers of Kamarkhanda Upazila (sub-district) under Sirajganj district. According to the findings of the study, livestock farming has significant contributions in improving the status of livelihood tatus of farming households. It is evident from the findings that majority of the respondents (69%), faced medium level of challenges in livestock farming compared to high level of challenges faced by 28% respondents of the study area. The socio-demographic characteristics of the respondents namely farm size, annual income, training received, subsidy received and extension media contact seem to have significant contributions with the challenges faced by the farmers in livestock farming. As the livestock sector of Bangladesh has great potential to flourish provided the challenges faced by the farmers are given due attention. Implementation of farmers’ friendly livestock policy and the collaborative efforts of public and private sectors are required to boost up livestock productivity in Bangladesh. SAARC J. Agric., 20(1): 209-225 (2022)